2014
DOI: 10.1007/s11695-014-1244-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Conservative Management for Gastric Perforation Secondary to Intragastric Balloon Possible? Case Report and Review of Literature

Abstract: Intragastric balloon (IGB) is one of the available options for the management of morbid obesity. The procedure is generally safe and of moderate efficacy in most of the cases. One of the reported complications of IGB is gastric perforation. The management of this complication is classically surgical. To our knowledge, conservative management for gastric perforation secondary to IGB has not been reported. A 27-year-old female patient presented with sudden abdominal pain in the left upper quadrant, 2 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The balloon might exert excessive pressure on the gastric wall, with subsequent erosion, ulcer, or eventual perforation [8]. Our case is the first report of late gastric perforation after adjustable IGB placement.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The balloon might exert excessive pressure on the gastric wall, with subsequent erosion, ulcer, or eventual perforation [8]. Our case is the first report of late gastric perforation after adjustable IGB placement.…”
Section: Discussionmentioning
confidence: 78%
“…Late IGB-induced gastric perforation is a very rare complication, reported explicitly in only six previous cases of nonadjustable IGB [4][5][6][7][8]. The balloon might exert excessive pressure on the gastric wall, with subsequent erosion, ulcer, or eventual perforation [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after review of cases in the literature (Table 1), including the three cases in the present series, we found death of three out of 18 patients who presented with gastric perforation following IGB insertion (16.6 %). Such a high mortality rate raises doubts about the above recommendation by Bekhit M. et al [24].…”
Section: Discussionmentioning
confidence: 92%
“…Genco A. et al reported two cases in the Italian experience that were managed laparoscopically among five cases of gastric perforation [10], and later another case was reported showing the simultaneous procedure by an endoscopist and a surgeon in management [20]. On the other hand, Bekhit M. et al reported one case of successful conservative management of gastric perforation secondary to intragastric balloon insertion and concluded that such perforations can be treated conservatively in highly selected patients [24]. However, after review of cases in the literature (Table 1), including the three cases in the present series, we found death of three out of 18 patients who presented with gastric perforation following IGB insertion (16.6 %).…”
Section: Discussionmentioning
confidence: 99%